2015
DOI: 10.1017/s1368980015003407
|View full text |Cite
|
Sign up to set email alerts
|

Development and calibration of a dietary nitrate and nitrite database in the NIH–AARP Diet and Health Study

Abstract: Objective Nitrate and nitrite are probable human carcinogens when ingested under conditions that increase the formation of N-nitroso compounds. There have been limited efforts to develop US databases of dietary nitrate and nitrite for standard FFQ. Here we describe the development of a dietary nitrate and nitrite database and its calibration. Design We analysed data from a calibration study of 1942 members of the NIH–AARP (NIH–AARP, National Institutes of Health–AARP) Diet and Health Study who reported all f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 59 publications
0
53
0
2
Order By: Relevance
“…19 The results of a calibration study of nitrate and nitrite intakes, conducted in a subset of the cohort, showed that the performance of the DHQ in assessing dietary nitrate and nitrite intakes was comparable to that for many other macronutrients and micronutrients (for example, the adjusted correlation coefficient for animal nitrite was 0.52 for women and 0.64 for men). 19 Cohort follow-up and outcome ascertainment Follow-up time extended from the date the baseline questionnaire was returned to the date of death or 31 December 2011. We confirmed vital status by annual linkage of the cohort to the Social Security Administration Death Master File in the US verification of vital status, and cause of death information came from follow-up searches of the National Death Index.…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…19 The results of a calibration study of nitrate and nitrite intakes, conducted in a subset of the cohort, showed that the performance of the DHQ in assessing dietary nitrate and nitrite intakes was comparable to that for many other macronutrients and micronutrients (for example, the adjusted correlation coefficient for animal nitrite was 0.52 for women and 0.64 for men). 19 Cohort follow-up and outcome ascertainment Follow-up time extended from the date the baseline questionnaire was returned to the date of death or 31 December 2011. We confirmed vital status by annual linkage of the cohort to the Social Security Administration Death Master File in the US verification of vital status, and cause of death information came from follow-up searches of the National Death Index.…”
Section: Methodsmentioning
confidence: 96%
“…19 We multiplied the nitrate and nitrite composition of each DHQ processed meat item by the reported frequency of consumption and portion size and summed this across all processed meat items. 19 The results of a calibration study of nitrate and nitrite intakes, conducted in a subset of the cohort, showed that the performance of the DHQ in assessing dietary nitrate and nitrite intakes was comparable to that for many other macronutrients and micronutrients (for example, the adjusted correlation coefficient for animal nitrite was 0.52 for women and 0.64 for men). 19 Cohort follow-up and outcome ascertainment Follow-up time extended from the date the baseline questionnaire was returned to the date of death or 31 December 2011.…”
Section: Methodsmentioning
confidence: 99%
“…37 A similar approach to estimate nitrate and nitrite levels from a FFQ found good correlations with 24 hour-based recalls for women. 38 For each participant, we estimated dietary nitrate and nitrite overall and separately for intakes from plant, animal, and processed meat (e.g., sausage, salami, bologna; bacon; and hot dogs) sources. We multiplied the frequency of consumption of vitamin C-containing foods and dietary supplements by their vitamin C levels to generate total intake, and similarly estimated intake of vitamin E, another antioxidant and potential inhibitor of endogenous nitrosation.…”
Section: Methodsmentioning
confidence: 99%
“…reduces the amount of nitrates by 10 % on average [17]. Washing potato, carrot, table beet, cabbage for 1 hour decreases the level of nitrates by 25-30 %; greenery (parsley, celery, spinach, dill, green onion) -by 20 % [18,19]. However, water-soluble nutrients are also partially lost during treatment.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%